More to Explore: Further Definition of Risk Factors for COPD – Differential Gender Difference, Modest Elevation in PM2.5, and e-Cigarette Use - Zhang, Yixuan; Wang, Lu; Mutlu, Gökhan M.; Cai, Hua (Frontiers in Physiology, 2021)
Chronic obstructive pulmonary disease (COPD) is a severe respiratory disease with high morbidity and mortality, representing the third leading cause of death worldwide. Traditional risk factors for COPD include aging, genetic predisposition, cigarette smoking, exposure to environmental pollutes, occupational exposure, and individual or parental respiratory disease history. In addition, latest studies have revealed novel risk factors. In this review, differential gender difference as a factor for COPD development at different territories is discussed for the first time. Women seem to have more COPD, while more women die of COPD or have more severe COPD, in Western societies. This seems different from the impression that COPD dominants in males which is true in Eastern societies. It might be related to higher rate of cigarette smoking in women in developed countries (i.e. 12.0% of women in US smoke vs. 2.2% in China). Nonetheless, women in Eastern societies are exposed to more biomass usage. Secondly, modest elevation in PM2.5 levels at ~25-50 µg/m3, previously considered “cleaner air”, is associated with incidence of COPD, indicating that more stringent goals should be set for the reduction of PM2.5 levels to prevent COPD development. Last but not least, e-cigarette use, which has become an epidemic especially among adolescents as officially declared by the US government, has severe adverse effects that may cause development of COPD early in life. Built upon an overview of the established risk factors for COPD primarily focusing on cigarette smoking and environmental pollutions, the present review further discusses novel concepts, mechanisms and solutions evolved around the emerging risk factors for COPD discussed above, understanding of which would likely enable better intervention of this devastating disease.